Mercy towards decarceration: Examining the legal constraints on early release from prison. Issue 1 (17th December 2020) - Cox, Alexandra; Betts, Dwayne
There are close to seven million people under correctional supervision in the United States, both in prison and in the community. The US criminal justice system is widely regarded as an inherently unmerciful institution by scholars and policymakers but also by people who have spent time in prison and their family members; it is deeply punitive, racist, expansive and damaging in its reach. In this article, we probe the meanings of mercy for the institution of parole.